What is in a movie? - Tan, Juan Jie (2015)
Key frame extraction plays an important part in video analysis and management. A typical video is rich in content and normally will consist of 20 to 30 frames per second. However most of these videos would contain information that is not needed so instead of analyzing all the frames in the video, only the key frames are used for further processing. In this report, video key frame extraction based on colour histogram is discussed. The key frames are computed by calculating the colour histogram difference between the consecutive frames and those that exceed a threshold value would then be considered as key frames. Thereafter, a 3D representation of the results of the key frames would then be displayed, so that analysis and processing could be done.